Rosai Dorfman Disease with malignant transformation to Histiocytic Sarcoma: A diagnostic conundrum - Shilpi Thakur; Reema M. Abraham; Deepam Pushpam; Shamim Ahmed; Saumyaranjan Mallick (Wolters Kluwer Medknow Publications, 2024)
Histiocytic disorders mostly occur as de-novo nodal or extranodal benign masses with rare secondary malignant transformation. A 10-year-old female presented with 10-cm cervical swelling since 9 months associated with fever. Computed tomography revealed left cervical lymphadenopathy and bilateral lung nodules. Lymph node excision biopsy showed effacement of architecture by atypical histiocytes with marked nuclear pleomorphism and frequent mitosis. Focal areas showed mature histiocytes with emperipolesis. The cells were immunopositive for CD68, CD163, and S100 (focal), whereas they were negative for Langerin and CD1a. The Ki67 proliferative index was 30%. A diagnosis of histiocytic sarcoma in a background of Rosai-Dorfman disease was made.